The impact of difference of response pattern in electronic tests on the development of cognitive achievement among high school students in mathematics in Jeddah - Al - Salmi, Nawaf Abdullah Zaid (Journal of Educational and Psychological Sciences, 2017)
The objective of this research was to determine the response pattern (multiple drop-down / selection menu) suitable for use in the design of constructional electronic tests. To achieve the research objective, the researcher designed and produced a structured learning program, The experiment was conducted on a sample of students in the first grade of secondary school in Jeddah (60) students for the academic year 1437-1438. The random sample was divided into two experimental groups: the first group (the drop-down response pattern group), the second group Except The results showed no statistically significant differences at (0.05) between the mean scores of the group (drop-down response) and the selection response group The results of the research presented a number of recommendations, the most important being the ability to rely on any of the two types of response that were used in the research and proved the effectiveness of the development of knowledge achievement in the design of electronic tests.